A postfeminist portrayal of women in chick literature - Voon, Esther Suk Hsien (Universiti Malaysia Sarawak, UNIMAS, 2009)
The popularity of Helen Fielding’s Bridget Jones’s Diary in 1996 gave rise to the chick lit genre and transformed the world of contemporary women’s fiction. This study examines the portrayal of women in chick lit, and the portrayal of Becky Bloomwood in Sophie Kinsella’s Shopaholic series; whether women are typecast into particular roles and functions; and whether they are subjected to gender stereotypes, sexism and objectification. A literary analysis of the five books in the series is conducted using the postfeminist theoretical framework. This study revealed that Becky Bloomwood is depicted as a postfeminist heroine, evidenced by her dependence on men, repression of her identity as a result of marriage, and perception of weddings and married life. Women in chick lit are expected to fulfill their roles as wives and mothers, and are frequently depicted as victims of gender stereotypes, sexism and objectification. Findings of this study will add to existing knowledge of the message being conveyed to readers of chick lit, as well as the influence of gender in popular culture, literature and media.